End-of-pipe Waste Analysis and Integrated Solid Waste Management Plan - Adriel Alfred Umali Palomar; Marloe B. Sundo; Perlie P. Velasco; Donny Rey D. Camus (Salehan Institute of Higher Education, 2019)
A ten-year integrated solid waste management plan was established for the University of the Philippines Los Baños which complies with the provisions of RA 9003. An end-of-pipe Waste Analysis and Characterization Study (WACS) was performed to identify the classification of wastes in UPLB. Waste generation was found to be 593.67 kg/day on the average and is expected to increase by 2% per year which is 709.49 kg/day on the year 2027. The waste composition by weight of the non-biodegradable wastes are as follows: plastic (55.68%); paper (35.77%); glass bottles (5.22%); metal (2.77%); and residuals (0.55%). A large portion of the wastes, which is 99.45% by weight, are recyclables. The loose density of wastes is 131.93 kg/ m3. Feasible collection points were assigned to improve efficiency of the collection of wastes in the university. Building units inside the campus were clustered and was assigned to dispose wastes to a single temporary storage facility per cluster. There are 181 units of 240-L garbage bin needed for the 39 clusters in UPLB. Two sets of dimensions of a proposed temporary storage facility were provided for the temporary storage facility; 5 2 2.2 m and 3.5 2 2.2 m. Conceptual design and structural plans of the materials recovery facility were provided. Mass balance was performed, and the theoretical diversion efficiency of the materials recovery facility is 99.445%.